Reference data for engineers radio, electronics, computer, and communications. - Middleton, Wendy (Boston ; Oxford : Newnes, 2002)
Reference Data for Engineers is the most respected, reliable, and indispensable reference tool for technical professionals around the globe. Written by professionals for professionals, this book is a complete reference for engineers, covering a broad range of topics. It is the combined effort of 96 engineers, scientists, educators, and other recognized specialists in the fields of electronics, radio, computer, and communications technology. By providing an abundance of information on essential, need-to-know topics without heavy emphasis on complicated mathematics, Reference Data for Engineers is an absolute "must-have" for every engineer who requires comprehensive electrical, electronics, and communications data at his or her fingertips. Featured in the Ninth Edition is updated coverage on intellectual property and patents, probability and design, antennas, power electronics, rectifiers, power supplies, and properties of materials. Useful information on units, constants and conversion factors, active filter design, antennas, integrated circuits, surface acoustic wave design, and digital signal processing is also included. The Ninth Edition also offers new knowledge in the fields of satellite technology, space communication, microwave science, telecommunication, global positioning systems, frequency data, and radar. * Widely acclaimed as the most practical reference ever published for a wide range of electronics and computer professionals, from technicians through post-graduate engineers. * Provides a great way to learn or review the basics of various technologies, with a minimum of tables, equations, and other heavy math.
Radio frequency spectrum management and time frequency standards -- International telephony recommendations -- Units, constants, and conversion factors -- Properties of materials -- Components or parts -- Fundamentals of networks -- Fourier waveform analysis -- Filters, simple bandpass design -- Filters, modern-network-theory design -- Active filter design -- Attenuators -- Measurements and analysis -- Magnetic-core transformers and reactors -- Power electronics -- rectifiers, filters, and power supplies -- Feedback control systems -- Electron tubes -- Power grid-tube circuits -- Semiconductors and transistors -- Transistor circuits -- Integrated circuits -- Optoelectronics -- Optical communications -- Analog communications -- Digital communications -- Information theory and coding -- Computer communications networks -- Satellite and space communications -- Discrete-time signal processing -- Transmission lines -- Waveguides and resonators -- Scattering matrices -- Antennas -- Electromagnetic-wave propagation -- Radio noise and interference -- Broadcasting, cable television, and recording system standards -- Radar -- Radio navigation systems -- Common carrier transmission -- Switching networks and traffic concepts -- Electroacoustics -- Lasers -- Computer organization and programming -- Logic design -- Probability and statistics -- Reliability and life testing -- Cellular telecommunications systems -- Mathematical equations -- Mathematical tables -- Miscellaneous data.
Previous ed.: Carmel, Ind. : SAMS, 1993.
Includes bibliographical references and index.
Keywords: Electronics; Computer engineering; Telecommunication; Electronic books